Effect of properties of activated carbon on malachite green adsorption. (1st August 2019) - Qu, Wenyuan; Yuan, Tong; Yin, Guojun; Xu, Shiai; Zhang, Qing; Su, Hongjun
Graphical abstract: Highlights: Malachite green adsorption behavior on four types of commercial activated carbons was studied. The effect of pore and surface chemical properties for malachite green adsorption is confirmed. Malachite green adsorption performance on activated carbon depends on the total specific surface area. Abstract: Malachite green (MG) separation from wastewater has always been a research focus in the field of environment. Removal of MG from aqueous solution using activated carbon has been studied or verified. Because of the different preparation materials and processes, the physicochemical properties of activated carbons differ significantly, and it is not clear which parameter affects on MG adsorption and to what extend it is. Four types of commercial activated carbon were selected to study their MG adsorption performances systematically, such as adsorption contact time, equilibrium adsorption capacities, Langmuir and modified Langmuir equations fitting, adsorption thermodynamics and effect of pH. The study of contact time showed that MG adsorption on four activated carbons fits the pseudo-second-order equation in the initial stage. However, the adsorption kinetics is found to follow pseudo-first-order equation with the increase of adsorption capacities. Consistent with the results reported in the literature, the adsorption mechanism of MG on activated carbon is monolayer physisorption. We associated MG adsorption behavior on four activated carbons with the specific surface area from different pore structures and content of surface chemical groups, respectively. The results showed that the strong acidic groups have the detrimental influence on the MG adsorption, while the total specific surface area has a notable effect, showing a positive linear relationship between the total specific surface area and the adsorption capability. Therefore, the total specific surface area could be used as a key parameter to determine the adsorption performance of MG on activated carbon.